2019
DOI: 10.12659/msm.913630
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Integrated Fixation Cage Versus Anterior Cervical Plate and Cage in Anterior Cervical Corpectomy and Fusion (ACCF): A Finite Element Analysis

Abstract: Background Anterior cervical plate and cage fixation system (ACPC) used in anterior cervical corpectomy and fusion (ACCF) is reported to incur excess complications. This study aimed to introduce integrated fixation cage (IFC) into ACCF to eliminate the anterior cervical plate (ACP)-related complications. Material/Methods One validated intact and 3 ACCF-simulated C3–C7 cervical spine models were developed. In ACCF models, C5 was corpectomied and fixed by IFC or ACPC. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Therefore, the results obtained from the models described in this study should be interpreted with caution. It was not possible to completely duplicate the findings from in vivo studies using FE analysis [33]. Despite the above limitations, this study effectively demonstrated the biomechanical changes associated with the different shapes of cages in ACPC by maintaining the consistency of the experimental conditions of each ACPC model.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the results obtained from the models described in this study should be interpreted with caution. It was not possible to completely duplicate the findings from in vivo studies using FE analysis [33]. Despite the above limitations, this study effectively demonstrated the biomechanical changes associated with the different shapes of cages in ACPC by maintaining the consistency of the experimental conditions of each ACPC model.…”
Section: Discussionmentioning
confidence: 94%
“…With 3 or more level fusions, it is difficult to maintain lordotic alignment during surgery; Second, postoperative lordosis changes are likely lower because of the few remaining mobile segments after a 3-level arthrodesis; Third, all patients underwent ACDF with rigid plate augmentation. The anterior plate and screw system has a limited length and rigid motion even if the anterior cervical plate system provides immediate segmental stability, fixation strength, thereby increasing the fusion rate [29]. Taken together, these mechanisms explain the difficulty in achieving lordosis in 3-level arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…The FEA modeling method has been described in our previous study [9]. Briefly, the computed tomography (CT) images of the lower cervical spine were obtained from a healthy man (aged 31 years, 76 kg, and 177 cm) at 1-mm intervals.…”
Section: Methodsmentioning
confidence: 99%